Sexual Distance in Victim-Offender Relationships: Expanding the Social Distance Hypothesis for Rape Sentencing in China - Chen, Manting (Journal of quantitative criminology, 2025)
ObjectivesDrawing on the social distance hypothesis, this study investigates how sexual distance between victims and offenders affects sentencing outcomes in rape cases.MethodsThis analysis utilizes first-trial criminal sentencing documents for rape offenses from 2014 to 2019 in China, retrieved from the Chinese Judgements Online website, resulting in a final sample of 7,152 cases. Sexual distance is defined based on victim-offender relationships (VORs), with intimate partners being closest, followed by friends, acquaintances, and strangers, with family members being the most distant. In contrast, social distance places family members closer to intimate partners, followed by friends, acquaintances, and strangers. To examine the impact of VORs on sentencing outcomes, both dummy coding and repeated effect coding were applied to social and sexual distance in logistic models (for probation) and double-truncated negative binomial models (for sentence length).ResultsThe findings indicate that sexual distance, rather than social distance, positively influences rape sentencing outcomes. As the sexual distance between the victim and the offender decreases—from family members to intimate partners—the length of the sentence for the offender also decreases. Offenders who are sexually distant from their victims, particularly family members, receive significantly longer sentences than those who are sexually closer.ConclusionsSexual distance proves to be a powerful indicator of rape sentencing outcomes. By comparing the social and sexual distance indicated by VOR types, this study provides evidence of the influence of legal and cultural contexts on judicial decisions, thereby extending the social distance hypothesis.